AB1013 Development and validation of a flourescence optical imaging rheumatoid arthritis scoring system for synovitis in the wrist and hand. (15th June 2017) - Glinatsi, D; Østergaard, M; Terslev, L; Ohrndorf, S; Ammitsbøll-Danielsen, M
Abstract : Background: Fluorescence optical imaging (FOI) has been suggested as an imaging modality for assessment of inflammation (i.e. synovitis) in the hands, and has in several studies been compared to US and MRI, using different, but not validated scoring systems. Objectives: To develop and validate a semi-quantitative FOI RA scoring system for synovitis in the wrist and hand. Methods: 46 RA patients, eligible for induction or intensification of disease modifying anti-rheumatic drug and with ≥1 clinically swollen joint in the hand were included. FOI image-sets of both wrists and hands were obtained at baseline, and after 3 and 6 months' follow-up using a Xiralite system unit (nanoPET Pharma GmbH, Berlin, Germany). The patients received a bolus of i.v. indocyanine green (ICG) pulsion (1mg/kg body weight) 10 seconds after starting the examination, which obtained 1 image/second over 6 minutes. The image-sets were anonymized and randomized and were assessed for synovitis at the wrist, 1st-5th metacarpophalangeal, 1st interphalangeal and 2nd-4th proximal interphalangeal joint levels in both hands by two readers blinded to patient data but not chronology. 23 image-sets were re-anonymized and re-read for intra-reader agreement analysis. The scoring system for synovitis was based on the assumption that inflamed tissue would demonstrate a more rapid enhancement than surrounding tissues. For each joint, the images were assessed sequentially from start of the injection of ICG-pulsion to peak enhancement. At the peak enhancement, the color index was adjusted in order to increase the discrepancy between colors. Synovitis was defined as a sharply marginated enhancement with clear delineation from surrounding tissues and correct anatomical location lasting ≥3 seconds. The thickness of the pathology fulfilling these criteria was compared to the width of the joint in the transverse plane at the 3rd second of enhancement and the following semi quantitative scoring system (0–3) was applied: grade 0: no enhancement, grade 1: <1/3, grade 2: ≥1/3 but ?2/3, grade 3: ≥2/3 of joint thickness (range 0–66). Descriptive statistics and the Wilcoxon signed-rank test were used to assess change in score over time. Intra-/inter-reader for status and change scores were assessed using single measure intra-class correlation coefficients (ICC) and smallest detectable change (SDC, change scores only). Responsiveness was assessed using standardized response mean (SRM). Results: Median (IQR) total synovitis score at baseline was 9.5 (4.0;16.5) and improved with -5.0 (-10.0;-1.0) and -8.0 (-13.5;-3.0) at 3 and 6 months' follow up, respectively (p<0.01). Intra- and inter-reader ICCs were good to very good for total scores (Table 1 ). The SDCs were generally low and for the inter-reader SDCs, 56% and 60% of the patients had a change >SDC between baseline and 3 and 6 months, respectively. The mean SRM for total change scores at 3 at 6 months' follow-up were moderate to good (0.7 and 0.8). Conclusions: The novel FOI RA synovitis scoring system showed high reliability and moderate to good responsiveness in the wrist and hand. Future studies should focus on assessing the sensitivity and specificity of the FOI synovitis score with ultrasound and magnetic resonance imaging as gold standard. Disclosure of Interest: None declared